2018
DOI: 10.1080/2162402x.2018.1469594
|View full text |Cite
|
Sign up to set email alerts
|

VISTA is highly expressed on MDSCs and mediates an inhibition of T cell response in patients with AML

Abstract: Treatment of acute myeloid leukemia (AML) remains challenging. Enhancement of anti-tumor responses by blocking negative immune regulators is a promising strategy for novel effective leukemia therapeutics. V-domain Ig suppressor of T-cell activation (VISTA) is a recently defined negative regulator mediating immune evasion in cancer. To investigate the effect of VISTA on anti-leukemia immune response in AML, we initiated a study using clinical samples collected from AML patients. Here we report that VISTA is hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
109
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(110 citation statements)
references
References 41 publications
0
109
1
Order By: Relevance
“…We also found that normal human organs other than lymphoid tissues and placental trophoblastic cells did not express VISTA at the protein level [13]. Although VISTA protein has been detected in gastric cancer, oral squamous cell carcinoma, NSCLC, colorectal carcinoma, hepatocellular carcinoma, endometrial cancer, ovarian cancer, melanoma, and gestational trophoblastic neoplasia, its expression and relationship with patient survival vary according to the type of cancer [13][14][15][16][17][18][19][20][21]. While VISTA was mainly expressed by tumor-infiltrating lymphocytes, it was only present in 8.8% of gastric cancer cells and in 19.4-22.8% of NSCLC lesions [15,16].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…We also found that normal human organs other than lymphoid tissues and placental trophoblastic cells did not express VISTA at the protein level [13]. Although VISTA protein has been detected in gastric cancer, oral squamous cell carcinoma, NSCLC, colorectal carcinoma, hepatocellular carcinoma, endometrial cancer, ovarian cancer, melanoma, and gestational trophoblastic neoplasia, its expression and relationship with patient survival vary according to the type of cancer [13][14][15][16][17][18][19][20][21]. While VISTA was mainly expressed by tumor-infiltrating lymphocytes, it was only present in 8.8% of gastric cancer cells and in 19.4-22.8% of NSCLC lesions [15,16].…”
Section: Discussionmentioning
confidence: 76%
“…These studies suggest that VISTA may modulate a novel immune evasion mechanism and is thus a potential target for cancer immunotherapy. VISTA expression in human cancers has been reported in non-small cell lung cancer (NSCLC), hepatocellular carcinoma, colorectal carcinoma, oral squamous cell carcinoma, gastric carcinoma, acute myeloid leukemia, and gestational trophoblastic neoplasia [13][14][15][16][17][18][19][20][21]. Mulati et al also found that VISTA was highly expressed in human ovarian and endometrial cancers [20].…”
Section: Introductionmentioning
confidence: 98%
“…In VISTA‐deficient mice, B16‐OVA melanoma and CT26 colon cancer tumors grow with reduced kinetics , and VISTA‐deficient mice also show reduced susceptibility to GL261 glioma, particularly when undergoing radiation therapy . Cells mediating VISTA suppression may be of both the T cell and myeloid lineages . Myeloid‐derived suppressor cells (MDSC) from an LP‐BM5 virus model showed a significant dependence on VISTA for suppressive function .…”
Section: The Promise Of Vista In Cancer Immunotherapymentioning
confidence: 99%
“…An expansion in the number of MDSCs has been reported in AML patients, where they inhibit T cell responses (53)(54)(55)(56). Expansion of MDSC decreases CAR T cell efficacy in solid tumors (57), and interventions that aim to inhibit MDSC function have had preclinical success in improving CAR T cell function (58).…”
Section: Myeloid-derived Suppressor Cellsmentioning
confidence: 99%